NATURAL WAYS OF MOVING AS BASIS OF MOTORICAL DEVELOPMENT WITH KINDERGARTEN CHILDREN - Bećir Šabotić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
Nowdays, the physical culture has become like an existing need for people.in everyday life people most often use the natural ways of moving like walking and running. The natural ways of moving are given and defined by the nature itself, anatomic-physiological and even phychological factors. Besides natural ways there are constructed ways which are more complex and which are taken out from the natural ones. The first thing, child does when is born, is to turn around, climb up, walk, run, jump, climb up the trees, throw, carry etc. These are the basic ways of moving that will say of natural moving. The natural ways of moving are used in PE in kinderkarten as we; as in the earlier grades in primary schools. They represent: - Spontaneous or conscious, forcable or free changes of mechanical state (condition and place) human body or just some of his particular parts in the space out of it. - They are accomplished with the complex physical-chemical process of change (circulation) of matter and energy inside the body, as well as between it and outer environment. Everyday moving is in the function existing, working-productive or devensively appropriate: we walk to come to a certain place, came and runaway, rising hand to reach for something, to give or take smthing etc. The aim of moves and moving in the physical exercises is consciously pointed on the inner physical changes and physical development of the organism.That is why the walking, which is used as a physical exercise, has no longer the purpose to the cariovascular and respiratoric system, strenghtening of the leg muscles etc.The natural ways of moving, as it appears in all domestic and foreign researches, with these children, effect very positevly on the development of bone system, cardiovascular, breathing device, muscular system and even on the positive development of organs and the whole organism. That is why these ways of moving are very much represented at this agethrough the elementary games, and by knowing the importance of games for these children we enable harmonical psychophysical development for everyone